Bimbingan Teknis: Strategi Menemukan Novelty Berbasis IT - Sujianto, Agus Eko; Hidayat, Muhammad Syahrul; Indriyani, Dwita; Asyifyan, Mirza Avicenna (Universitas Nusantara PGRI Kediri, 2024)
The main task of lecturers as part of the higher education academic community is the Tridharma of Higher Education: teaching education, research and community service. In the aspect of community service, lecturers are expected to have constructive programs that have positive externalities for both external and internal stakeholders who are of concern in this program. Internal stakeholders in this context are students, who have the duty and responsibility to produce highly competitive scientific work. To realize this competitiveness is the background for this community service program in the form of Technical Guidance designed in the form of Service Learning. The participants in the activity were students of the Postgraduate Sharia Economics Masters at UIN Sayyid Ali Rahmatullah Tulungagung. The results of this activity show that this technical guidance is able to influence students in finding Information Technology (IT) based novelties, and with this novelty the scientific work produced by students has high competitiveness.